Modernisasi Sistem Pendidikan Islam di Indonesia: Dari Awal Abad ke-20 hingga Periode Kontemporer - Dadan Adi Kurniawan (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
This study aims to determine the background and characteristics/forms of the modernization of the system of Islamic educational institutions in Indonesia from the beginning of its emergence to the contemporary period. The method used is a historical and qualitative method with a comparative approach. The results show that the milestones of modernizing Islamic education in Indonesia began to emerge in the early 20th century as a response to discriminatory Dutch colonial education as well as criticism of the traditional Islamic education system at that time which was considered less relevant to the demands of the times. Modernization of Islamic education offers a new system that is more accommodative, adaptive, and solutive. This modernization is still ongoing today with various variants of updates. The existence of modernization has provided a new breakthrough in the world of Islamic education in Indonesia, although at the same time some other Islamic educational institutions still maintain their traditional style.